Oral Fluids—A Diagnostic Tool for COVID-19: A Review - Ramesh, Amitha; Potdar, Raksha; Bhandary, Rahul (Journal of Health and Allied Sciences NU, 2021)
Global outbreak of coronavirus disease 2019 (COVID-19) in December 2019 has affected millions of people around the world. This virus binds to angiotensin-converting enzyme-2 receptors present in the pharynx, nose, oral cavity, salivary glands, tongue, etc. Saliva has been shown to have viral loads of COVID-19 as it reported to be 2019-novel-coronavirus nucleic acid positive. This article is based on the association of oral fluids and their role in diagnosis of coronavirus infection.
Keywords: COVID-19; saliva; gingival crevicular fluid